Las páginas personales como recurso informativo. - Alvite Díez, Mª Luisa (Revista General de Información y Documentación, 2001)
Personal web pages as an information source are vindicated on the consi deration that they are capable of overcoming the level of triviality generally accorded them. Starting from the premise that they should be recognized as pos sible candidates br inclusion in specialist guides and directories, the scientific literature on the evaluation of digital resources were analysed and parameters arid indicators established. These were then applied to a selection of personal pages dealing with a specific discipline: the Spanish language.This approach will, it is hoped, contribute towards the systematization of information available ibe web.
Keywords: Personal pages; digital resources; digital resources evaluation; spanish lan guage